2019
DOI: 10.1111/pre.12404
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and morphological adaptation of Halimeda opuntia (Bryopsidales, Chlorophyta) to light intensity

Abstract: Plasticity gives plants the ability to adapt their morphology and growth to various environments. Environmental factors can lead to changes in the growth forms of algae. Halimeda opuntia was used as a model organism to determine the effects of highly irradiated and shade conditions in the field and its responses to low light conditions in the laboratory, which are known to be some of the main factors driving its morphological plasticity. To investigate the morphological and anatomical characteristics of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The segments themselves are usually also highly variable within and among individuals of the same species. This variation is related to their position on the thallus [7], which may also be caused by environmental heterogeneity [8][9][10]. Recently, it has been shown that morphological variation of H. tuna segments is tightly constrained by the allometric size-to-shape relation [11].…”
Section: Morphometric Analysis Of Surface Utriclesmentioning
confidence: 99%
“…The segments themselves are usually also highly variable within and among individuals of the same species. This variation is related to their position on the thallus [7], which may also be caused by environmental heterogeneity [8][9][10]. Recently, it has been shown that morphological variation of H. tuna segments is tightly constrained by the allometric size-to-shape relation [11].…”
Section: Morphometric Analysis Of Surface Utriclesmentioning
confidence: 99%
“…These are apical, non-calcified segments and those from the basal part of the thallus that deviate from the species-typical shape. Plasticity of segment shape in response to environmental factors such as light availability ( Neustupa & Nemcova, 2018 ; Pongparadon, Nooek & Prathep, 2020 ) or wave exposure ( Littler & Littler, 2000 ; Kooistra & Verbruggen, 2005 ; Pongparadon, Nooek & Prathep, 2020 ) has also been described.…”
Section: Introductionmentioning
confidence: 99%
“…In general, calcification rate in Halimeda spp. is influenced by rate of photosynthesis, light, and nutrient availability ( Vroom et al, 2003 ; Yniguez, McManus & Collado-Vides, 2010 ; Pongparadon, Nooek & Prathep, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both species, however, have photosynthetic segments that are protected with a calcium carbonate layer, which might confer better resilience under environmental stress(Wei et al 2020). In addition, H. opuntia has been shown to survive in stressful conditions through the development of segment plasticity(Pongparadon et al 2020).Information on oceanographic conditions within Silot Bay is limited. Nonetheless, the impact of changes in oceanographic conditions over the years on algal flora within the bay may be inferred from observations made in other studies around the world.…”
mentioning
confidence: 99%